This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try
refreshing the page, (b) enabling javascript if it is disabled on your browser and,
finally, (c)
loading the
non-javascript version of this page
. We're sorry about the hassle.
The answer is e.
Here is a solution. Let P ( n ) = ∏ k = 1 n ( 1 + t k 1 )
We can write each factor in our product series as
( 1 + t k 1 ) = ( t k t k + 1 ) = ( ( k + 1 ) × t k t k + 1 )
As a result we have :
P ( n ) = ( 2 × t 1 t 2 ) × ( 3 × t 2 t 3 ) × . . . × ( n × t k − 1 t n ) × ( ( n + 1 ) × t N t n + 1 )
= n + 1 ) ! t n + 1
Now let T ( n ) = ∑ k = 0 n k ! 1
We will show that T ( n ) = P ( n ) for all n ≥ 1 by induction on n
Here is our base case for n = 1
T ( 1 ) = 0 ! 1 + 1 ! 1 = 2 = ( 1 + 1 1 ) = P ( 1 )
Now we'll suppose T ( m ) = P ( m ) for some m and use this to show that
T ( m + 1 ) = P ( m + 1 ) . So
T ( m + 1 ) = T ( m ) + ( m + 1 ) ! 1 , and we have
P ( m + 1 ) = P ( m ) ( 1 + t m + 1 1 ) = ( m + 1 ) ! t m + 1 ( 1 + t m + 1 1 )
= ( m + 1 ) ! t m + 1 + ( m + 1 ) ! 1
= T ( m ) + ( m + 1 ) ! 1 = T ( m + 1 )
Consequently T ( n ) and P ( n ) have the same limit as N → ∞
and since lim n → ∞ T ( n ) = e we also have :
lim n → ∞ P ( n ) = e
Let me know if there are any mistakes or anything is unclear!